2006
DOI: 10.1093/bioinformatics/btl121
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased pattern detection in microarray data series

Abstract: Here we introduce a new method of detecting pattern in microarray data series which is independent of the nature of this pattern. Our approach provides a measure of the algorithmic compressibility of each data series. A series which is significantly compressible is much more likely to result from simple underlying mechanisms than series which are incompressible. Accordingly, the gene associated with a compressible series is more likely to be biologically significant. We test our method on microarray time serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…However, identifying the set of periodically expressed genes is a non-trivial endeavor and has been the subject of intense study. 1,[14][15][16][17][18] Three separate studies have reported global time-series transcription data across the mitotic cell cycle, and generated unique lists of periodically transcribed genes. 1,17,18 The overlap between these published lists is surprisingly small (see Suppl.…”
Section: Identifying Periodic Genesmentioning
confidence: 99%
“…However, identifying the set of periodically expressed genes is a non-trivial endeavor and has been the subject of intense study. 1,[14][15][16][17][18] Three separate studies have reported global time-series transcription data across the mitotic cell cycle, and generated unique lists of periodically transcribed genes. 1,17,18 The overlap between these published lists is surprisingly small (see Suppl.…”
Section: Identifying Periodic Genesmentioning
confidence: 99%
“…Examples include cyclic patterns such as those encountered in the Spellman alphafactor synchronization yeast cell-cycle experiment. At this point, it might be necessary to point out certain resemblance between the zero-crossing analysis and the complexity maps proposed in [12]. The first-order crossing order crossings obtained repeated application of the difference operator (high-pass filter) [5].…”
Section: Spectral Analysis By Zero-crossingmentioning
confidence: 99%
“…On closer observation, we note subtle differences in their definitions. The complexity maps [12] use (i) ranks of the values as opposed to the sign of the meansubtracted values (1).…”
Section: Spectral Analysis By Zero-crossingmentioning
confidence: 99%
See 2 more Smart Citations